H.I.V.E. Dreadnought - Walden, Mark (Simon & Schuster Books for Young Readers, 2012)
While Otto, Wing, and the other students at H.I.V.E. continue their education, a member of the world's most powerful group of villains lays down his plans for a worldwide Armageddon that places him at the head of a new world order. Before long, Otto, Wing, and the others are being dragged into this conflict, with everything they know at stake.